1986
DOI: 10.1093/ajcn/43.5.844
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phosphorus on endogenous fecal calcium excretion in man

Abstract: The effect of phosphorus on the endogenous fecal calcium excretion was investigated in man by administering tracer doses of 47Ca intravenously in control studies and during phosphorus supplementation. The phosphorus intake was approximately 800 mg/day in control studies and 2000 mg during phosphorus supplementation of the constant diet. The studies were carried out during different calcium intake levels of approximately 200, 800, 1300, 2000, and 2600 mg/day. Following the dose of 47CaCl2, the values of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Eleven studies assessed the effect of supplemental dietary phosphate salts administered orally, while one administered the phosphate intravenously [ 35 ], on urine calcium over 24-hours in healthy adults [ 21 , 27 - 34 , 36 , 37 ]. Eight of the studies examined calcium balance over one to 66 days [ 21 , 27 , 28 , 30 - 34 ] and one assessed calcium balance among only four of the seven subjects [ 28 ]. Six studies examined the effect of dietary phosphate supplements on bone turnover markers [ 29 , 31 - 33 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies assessed the effect of supplemental dietary phosphate salts administered orally, while one administered the phosphate intravenously [ 35 ], on urine calcium over 24-hours in healthy adults [ 21 , 27 - 34 , 36 , 37 ]. Eight of the studies examined calcium balance over one to 66 days [ 21 , 27 , 28 , 30 - 34 ] and one assessed calcium balance among only four of the seven subjects [ 28 ]. Six studies examined the effect of dietary phosphate supplements on bone turnover markers [ 29 , 31 - 33 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the present study was designed to examine conditions similar to the modern diet, we did not include two intervention arms (one arm in each of two studies [ 30 , 34 ]), as the subjects were given very high calcium intakes (2700 & 2600 mg/day, 68 & 65 mmol/day). These are greater than the Tolerable Upper Limit of the Institute of Medicine Dietary Reference Intake for calcium [ 24 ], and therefore we considered them experimental.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the regression equation obtained, and assuming that it is still valid in our narrow range of P intake, an increase of 400 mg/d P intake would give an increase of 17 mg TIC and, after correction for absorption, an increase of 12 mg endogenous faecal Ca. In a more recent and complete critical study of the determinants of endogenous Ca faecal loss in healthy women, the same authors (Heaney & Recker, 1994) criticised the opposite results obtained by Spencer et al (1986), who did not see any effect of a large intake of P (2000 mg v. 850 mg/d) on endogenous Ca faecal loss. Their revised regression coefficient was higher (6 mg TIC for 100 mg P intake), but, in the same study, an opposite relation was found between TIC and N intake: a diminution of 3 mg per g N, i.e.…”
Section: Consequence For Ca Balancementioning
confidence: 97%
“…Ad16. The respective sentence in Section 4.1 of the draft Opinion was rephrased to "The French Food Safety Agency (Afssa, 2001) applied the factorial method and considered daily obligatory losses in urine (130 mg), faeces (110 mg) and sweat (20 mg) (Spencer et al, 1986;Charles et al, 1991;Lemann, 1993;Heaney and Recker, 1994)".…”
Section: Panel Consideration Of Comments Receivedmentioning
confidence: 99%